Application of Innovative Power Electronic Technologies - Lai, Ching-Ming; Liu, Yitao (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This topic reprint "Application of Innovative Power Electronic Technologies" encompasses a diverse range of topics and discoveries that addresses the increasing global demand for energy conversion in the context of sustainable energy, electric vehicles, industrial automation, and smart grids. This reprint brought together a selection of papers that delve into new technologies and practical applications of power electronics, offering insights into the challenges and solutions faced in the design and implementation of advanced energy conversion techniques.